INCIDENCES DES LIMITES TERRITORIALES SUR LA SECURITE A L’EST DE LA REPUBLIQUE DEMOCRATIQUE DU CONGO - ATUBA, Jules MAGBAY (IJRDO - Journal of Social Science and Humanities Research, 2021)
The article is written in order to propose views about origines and consequences of the insecurity persisting in the Eastern part of the Democratic Republic of the Congo; the insecurity due to the porosity of its boundaries and all other bordering litigations that oppose the Democratic Republic of the Congo to its neighbours of the East. The mechanism that would permit stability and sustainable peace in that part of the country (Democratic Republic of the Congo) will also be tackled in here.